2016
DOI: 10.1515/jpem-2015-0354
|View full text |Cite
|
Sign up to set email alerts
|

GCK mutations in Chinese MODY2 patients: a family pedigree report and review of Chinese literature

Abstract: The thorough investigation of three Chinese families with MODY2 revealed two novel mutations and one known mutation. GCK gene sequencing helps in MODY2, especially when there is uncertain IFG or IGT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We found GCK mutations in nine out of eleven children with asymptomatic hyperglycaemia in our hospital cohort. There is a recent report from another children’s hospital in China, where three families with genetically confirmed MODY2 were diagnosed in over a year, two probands were children with asymptomatic hyperglycaemia and had abnormal OGTT [ 18 ]. These observations suggest that GCK mutations may be a common cause of asymptomatic hyperglycaemia in Chinese children.…”
Section: Discussionmentioning
confidence: 99%
“…We found GCK mutations in nine out of eleven children with asymptomatic hyperglycaemia in our hospital cohort. There is a recent report from another children’s hospital in China, where three families with genetically confirmed MODY2 were diagnosed in over a year, two probands were children with asymptomatic hyperglycaemia and had abnormal OGTT [ 18 ]. These observations suggest that GCK mutations may be a common cause of asymptomatic hyperglycaemia in Chinese children.…”
Section: Discussionmentioning
confidence: 99%
“…4) R191W: This variant has been reported in patients and families with clinical feature of GCK-MODY (supplementary ref 18,19,23,25). The functional studies showed that R191W was kinetically inactivating, with a decreased rate of catalysis and decreased affinity for glucose (supplementary ref 25).…”
mentioning
confidence: 99%